Pengaruh Disiplin dan Kompensasi Non Financial terhadap Kinerja Personel Disdikal melalui Kepuasan Kerja sebagai Variabel Moderating - Djasno, Donyanto Anis; Subeno, Bambang; Artanto, Ari (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study aims to analyze the influence of discipline and non-financial compensation on the performance of Disdikal personnel with job satisfaction as a moderating variable. The background of this study is based on the problem of low levels of discipline and limited non-financial compensation that can have an impact on decreasing personnel performance in the Indonesian Navy. The method used in this study is quantitative. The instrument used is a questionnaire distributed to 80 respondents. The data processing technique used was SEM with Smart PLS 4 software. The data obtained were analyzed using regression techniques to test the relationship between discipline variables, non-financial compensation, job satisfaction, and performance. The results of this study indicate that there is no strong influence of discipline on performance with a t-statistic value of 0.249 <1.64 and p-values> 0.05, there is a fairly strong influence of non-financial compensation on performance with a value of 3.654>1.64 and p-values ??<0.05, there is a strong influence of discipline on job satisfaction with a t-statistic value of 4.439 <1.64 and p-values ??<0.05, there is a strong influence of non-financial compensation on job satisfaction with a value of 7.511>1.64 and p-values ??<0.05, there is a fairly strong influence of job satisfaction on performance with a t-statistic value of 2.972>1.64 and p-values ??<0.05, there is an influence of discipline on performance through job satisfaction with a t-statistic value of 2.657>1.64 and p-values ??<0.05 and there is a fairly strong influence of non-financial compensation on performance through job satisfaction with a t-statistics value of 2.644> 1.64 and p-values ??<0.05. Therefore, the recommendations given to the Indonesian Navy to pay attention to this aspect as part of efforts to improve personnel performance in supporting the operational tasks of the Indonesian Navy and the results of this study are also used as input for Disdikal Personnel in improving personnel performance and satisfaction through discipline and non-financial compensation.